New reagents for the spectrophotometric determination of ranitidine hydrochloride - Narayana, Badiadka; Veena, Kunnummel; Ashwani, Krishnamurthy; Shetty, Divya Narayana (Eclética Química, 2010)
A new spectrophotometric method is proposed for the assay of ranitidine hydrochloride (RNH) in bulk drug and in its dosage forms using ceric ammonium sulphate (CAS) and two dyes, malachite (MAG) green and crystal violet (CV) as reagents. The method involves the addition of a known excess of ceric ammonium sulphate to ranitidine hydrochloride in acid medium, followed by the determination of unreacted CAS by reacting with a fixed amount of malachite green or crystal violet and measuring the absorbance at 615 or 582 nm respectively against the reagent blank. The Beer’s law is obeyed in the concentration range of 0.4-8.0 μg/ml of ranitidine hydrochloride (RNH) for RNH-MAG system and 0.2-1.6μg/ml of ranitidine hydrochloride for RNH-CV system. The molar Absorptivity, Sandell’s sensitivity for each system were calculated. The method has been successfully applied to the determination of ranitidine hydrochloride in pure and dosage forms.